Empirical analysis of Macedonian export structure: the role of metal industry - Lazarov, Darko; Kocovski, Mitko (Industrija, 2017)
The paper investigates the Macedonian export structure and export performance by using several indexes: product complexity, export sophistication, export diversity, and export ubiquity for the period 1995-2014. The empirical analysis is based on the application of product space methodology (based on network theory) developed by Hidalgo et al. (2007) with data from UN comtrade database. Moreover, the paper analyzes the performance of metal industry and its productivity as one of the biggest exporting sector and investigates its capacity for further product diversification. The estimated results indicate that Macedonian export basket is highly concentrated (the top ten products have nearly half of the total country’s export and more than 70 percent of the export goes to several countries) and more importantly the export structure is composed of  products with low complexity level. Additionally, the results show that the export structure is less diversified, making the economy very sensitive on the external shocks. On the other side, the analysis of metal industry performance indicates that this industry has comparative advantages (RCA=2.16) and more importantly it has strong capacity for further diversification by building new capabilities for production of more complexed products. So, the suggestion to policymakers in Macedonia is to be created an active industrial policy that will stimulate the structural transformation of metal industry towards products with higher value added.
Keywords: Economic Growth; Macedonian; Export